Adverse childhood experiences are associated with increased overdose risk in predominately Latinx adults seeking treatment for substance use disorders - Tschampl, Cynthia A.; Canuto, Melisa; De Jesús, Diliana; D'Ippolito, Melinda; Guzman, Micaurys; Larson, Mary Jo; Stewart, Emily; Lundgren, Lena (Frontiers in Psychiatry, 2022)
Introduction: Almost no previous studies explored the relationship between adverse childhood experiences (ACEs) and overdose risk for individuals with substance use disorders (SUDs), and these did not focus on a Latinx population. This study examined the relationship between ACEs, reporting PTSD symptoms, and lifetime experience of overdose in a sample (n=149) of primarily Latinx adults seeking treatment for substance use disorder (SUD). Materials and Methods: Administrative data from an integrated behavioral health and primary care treatment system in Massachusetts were analyzed through bivariate analyses and multiple logistic regression. The final model examined the association between self-reported ACEs, PTSD screen, and lifetime drug overdose. We controlled for demographic characteristics and heroin use and explored alternative measure specifications. Results: ACEs scores were high with 58% having experienced 4+ ACEs. Female gender was associated with a 24% higher ACE score than male gender (p<0.01). In the multiple logistic model each additional ACE was associated with 1.3 times greater odds of overdose (p<0.01). Those reporting heroin use had 8.8 times greater odds of reporting overdose compared to those reporting no heroin use (p<0.001). Gender, age, Puerto Rican ethnicity, years of cocaine use, receiving public assistance income, and a positive initial PTSD screen were not significant. Findings were robust in sensitivity testing. Discussion and Conclusion: We found the number of ACEs and reported heroin use significantly and positively associated with self-report of overdose in both bivariate and multiple logistic regression analyses. In contrast, a positive initial screen for PTSD was only significantly associated with overdose in the bivariate analysis. Increased screening for ACEs is warranted and ACE-specific treatment is suggested for SUD treatment programs offering trauma-informed services for adults.